Experimental Study on Gas Permeability Semiempirical Model of Granite after Heat Treatment - Jinquan Wu (Advances in Civil Engineering)
High temperature will cause a thermal crack of a rock, thus affecting the permeability change of rock. To explore the effects of temperature on permeability and microstructure of rock microstructure, the granite after 50–800 C thermal treatment was carried out by gas permeability test, combined with computed tomography (CT) scanning technology. The granite internal three-dimensional reconstruction was conducted after high-temperature thermal treatment, and the characteristics of the microstructure were also deeply analyzed. On this basis, the applicability of the Costa model under high temperature was discussed. Finally, the temperature-permeability model of granite after the high temperature was proposed combined with the pore fractal model. The new model was verified with experimental data.